2018
DOI: 10.1142/s1793431118500082
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Collapse Probability Considering Pounding and Financial Loss Estimation of Base-Isolated Reinforced Concrete Buildings

Abstract: In this paper, the seismic collapse probability of base-isolated reinforced concrete buildings considering pounding with a moat wall and financial loss estimation is studied. For this purpose, three-dimensional finite element models of a code-compliant 10-story base-isolated shear wall-frame (BI-SWF) building and a 10-story base-isolated moment resisting frame (BI-MRF) building are used. Results indicate that the BI-MRF building has a greater probability of collapse compared to that of the BI-SWF building, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…While a majority of studies were focused on seismic pounding between adjacent frame buildings, very few have addressed the effect of pounding on slender RC frame–shear wall (or simply termed “frame‐wall”) systems, 14,19 which are commonly used structural forms for tall buildings in modern urban areas. Fatahi et al 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a majority of studies were focused on seismic pounding between adjacent frame buildings, very few have addressed the effect of pounding on slender RC frame–shear wall (or simply termed “frame‐wall”) systems, 14,19 which are commonly used structural forms for tall buildings in modern urban areas. Fatahi et al 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Two ground motion records were adopted to demonstrate the seismic pounding effects on the distribution of internal forces and deflections along the piled buildings. Bhagat and Wijeyewickrema 19 showed that for base isolation systems, using RC frame‐wall buildings resulted in lower probability of collapse than using RC MRFs. It was shown that seismic pounding effects reduced the difference of the collapse probability between using the two stated structural systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation